Signs on the earth : Islam,Modernity and the Climate Crisis - Khalid, Fazlun M. (United Kingdom : Kube Publishing, 2019)
"An examination of reports from around the world involving Virgin Mary apparitions, UFO sightings, and crop circle formations. Focusing his study on a few global "hot spots," Leviton explains why these events happen, how the phenomena are connected, and, how they relate to the future of the Earth"--Provided by publisher.
Introduction: signs on the earth-apocalypse or a planet being reborn? -- The earth's big secret-our planet's visionary geography as a cosmic message board -- Part I: Light in the blood : Marian apparitions as preparations for our rebirth through the earth's visionary geography -- Everywhere, the woman clothed in the sun-discerning the where of Marian apparitions -- The message of the Virgin Mary's global presence-understanding the why of the apparitions -- Part II: Cloud of smoke : UFO and ET visitations-an irruption of the galaxy into the world around us -- Cosmopolitan earth : the implicit planetary reality of extraterrestrials -- UFO hotspots-is there a geomantic basis for alien encounters? -- Part III: A pillar of fire : crop circles-a language of light in Albion's golden band -- Crop circles-what is the message of these whorled patterns in the grain? -- How to get your head above the clouds in three steps.
Includes bibliographical references and index.
Keywords: Human ecology -- islam